Speeding up finite step-size updating of full QCD on the lattice - Hasenbusch, Martin (Physical review. D, Particles, fields, gravitation, and cosmology, 1999)
We propose various improvements of finite step-size updating for full QCD on the lattice that might turn finite step-size updating into a viable alternative to the hybrid Monte Carlo algorithm. These improvements are noise reduction of the noisy estimator of the fermion determinant, unbiased inclusion of the hopping parameter expansion and a multi-level Metropolis scheme. First numerical tests are performed for the 2 dimensional Schwinger model with two flavors of Wilson fermions and for QCD with two flavors of Wilson fermions and Schrödinger functional boundary conditions.